2013
DOI: 10.3329/dujps.v12i1.16294
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Community Pharmacists on Self-medication Management among Rural Dwellers, Kwara State Central, Nigeria

Abstract: ABSTRACT:The role of pharmacist has not only advanced from medication dispensing but also to direct patient care and pharmaceutical interventions aiming at enhancing the populace wellbeing. The objective of this research was to assess the impact of rural community pharmacist interventions on self-medications and disease prevalence among rural settings in the Kwara State Central, Nigeria. A descriptive, cross-sectional study was conducted in eight rural communities with a pre-piloted questionnaire. Data obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…A total of 4798 unique titles were screened, of which 19 [ 1 , 17 34 ] fulfilled eligibility criteria for inclusion in the review ( Fig 1 ). All eligible papers were published in English language.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 4798 unique titles were screened, of which 19 [ 1 , 17 34 ] fulfilled eligibility criteria for inclusion in the review ( Fig 1 ). All eligible papers were published in English language.…”
Section: Resultsmentioning
confidence: 99%
“…One study utilised an RCT design [ 18 ] and the remainder (n = 18) used observational designs ( Table 3 ). All included studies involved community pharmacy setting for which the clinical outcomes were measured [ 1 , 17 34 ]. Other settings, such as general practice [ 1 , 18 , 32 ] and EDs [ 1 ], were also included as comparators in measuring effectiveness against pharmacy-based management of minor ailments ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Information-gathering performed by pharmacy staff is not comprehensive, the advice provided to patients is often inappropriate, and most pharmacy staff fail to provide information regarding the medication sold [ 5 – 8 ]. As research has shown that providing appropriate advice when handling self-medication requests in community pharmacies can improve patient outcomes [ 9 11 ], it is important to improve the quality of counselling for self-medication in Indonesian community pharmacies.…”
Section: Introductionmentioning
confidence: 99%